Numerical analysis of a cell-based indirect internal reforming tubular SOFC operating with biogas - Nishino, T; Szmyd, J (2010)
A numerical study is performed on the thermal and electrochemical characteristics of a tubular solid oxide fuel cell (SOFC) employing the steam reforming of biogas in each individual cell unit but indirectly from the anode. The numerical model used in this study takes account of momentum, heat, and mass transfer in and around the cell, including the effects of radiation, internal reforming, and electrochemical reactions. The biogas, which is fed into the reformer with steam, is assumed to be composed of methane (CH4) and carbon dioxide (CO2). The results show that, under the conditions of a constant average current density of 400 mA/cm2 and a constant fuel utilization of 80%, the terminal voltage of the cell decreases but only moderately as the proportion of CH4 in the fuel supplied to the reformer is reduced. It is also shown that temperature gradients within the cell decrease as the proportion of CH4 in the supplied fuel is reduced. These results are promising for the future use of biogas for this type of indirect internal reforming SOFC system. Copyright © 2010 by ASME.